Ritual Chiamsi dan Sinkaw Budaya Etnis Tionghoa Konghucu - Juandi Rusdianto; Suzy S. Azeharie (Koneksi, 2020)
The study entitled Chiamsi Ritual and Sinkaw Chinese Konghucu Ethnic Culture was conducted to find out how the ritual process occurred when the Confucian Chinese community performed Chiamsi and Sinkaw. This research uses descriptive qualitative research method because it is considered the most appropriate to answer the research problem formulation titled Chiamsi Ritual and Sinkaw Chinese Konghucu Ethnic Culture. The study will use interviews with four informants who were divided into two key informants, experts in Sinology and two informants who carried out the rituals of Chiamsi and Sinkaw. The research data obtained were sourced from interviews, observations and literature studies. The theory used in this research is the theory of ritual communication from Deddy Mulyana and Yermia Djefri Manafe and the transcendental theory from Deddy Mulyana and Engkus Kuswarno. This study found the forecast using Chiamsi and Sinkaw is a ritual process carried out by ritual implementers to find out the picture or handle life as a solution to the problems of his life. At each step of the ritual Chiamsi and Sinkaw transcendental communication occurs between the gods and humans. Penelitian berjudul Ritual Chiamsi dan Sinkaw Budaya Etnis Tionghoa Konghucu dilakukan untuk mengetahui mengetahui bagaimana proses ritual yang terjadi saat masyarakat Tionghoa Konghucu melakukan Chiamsi dan Sinkaw. Penelitian ini menggunakan metode penelitian kualitatif deskriptif karena dianggap paling sesuai untuk menjawab rumusan masalah penelitian berjudul Ritual Chiamsi dan Sinkaw Budaya Etnis Tionghoa Konghucu. Penelitian akan menggunakan wawancara terhadap empat narasumber yang dibagi menjadi dua key informan ahli Sinologi dan dua informan pelaksana ritual Chiamsi dan Sinkaw. Data penelitian yang diperoleh bersumber dari wawancara, observasi dan studi pustaka. Teori yang digunakan dalam penelitian adalah teori komunikasi ritual dari Deddy Mulyana dan Yermia Djefri Manafe serta teori transendental dari Deddy Mulyana dan Engkus Kuswarno. Penelitian ini menemukan ramalan menggunakan Chiamsi dan Sinkaw merupakan proses ritual yang dilakukan pelaksana ritual untuk mengetahui gambaran atau pegangan hidup sebagai solusi atas masalah hidupnya. Pada setiap langkah ritual Chiamsi dan Sinkaw terjadi komunikasi transendental antara dewa dan manusia.